Réponses

  • Utilisateur Brainly
2014-09-14T22:10:55+02:00
(2x + 5)(3x - 1) - (2 - x)(x - 4)
= 6x² - 2x + 15x - 5 - (2x - 8 - x² + 4x)
= 6x² + 13x - 5 - 2x + 8 + x² - 4x
= 7x² + 7x + 3

(5x - 3)² - 2(x - 3)
= 25x² - 30x + 9 - 2x + 6
= 25x² - 32x + 15
Meilleure réponse !
2014-09-14T22:24:49+02:00

Bonsoir


On développe les deux expressions

A = (2x + 5)(3x - 1) - (2 - x)(x - 4)
   = 6x² - 2x + 15x - 5 - (2x - 8 - x² + 4x)
   = 6x² + 13x - 5 - 2x + 8 + x² - 4x

   = 6x² + x² +13x - 2x - 4x - 5 + 8
   = 7x² + 7x + 3

B = (5x - 3)² - 2(x - 3)
   = 25x² - 30x + 9 - 2x + 6

   = 25x² - 30x - 2x + 6 + 9
   =  25x² - 32x + 15